Vulnerabilidade social e contextos de vida: observação social sistemática para avaliação do risco de transmissão da dengue em Uberlândia-MG - Silva, Angelita Ferreira da (2018)
One of the basics premises of this research is that the place can reveal a lot about individual’s health who live there, indicating that the characteristics of the territory can be important to determinate the health conditions of a population. The objective of the present study was to study social vulnerability and life contexts by means of territorial observation to assess the risk of dengue transmission in Uberlândia-MG. Firstly, a correlation was established between areas of social vulnerability and incidence of dengue for the year 2016. Next, were studied two areas with elevated indices of social vulnerability and high incidence of dengue, the coverage areas of UBSF Alvorada and USBF Morumbi V to know the characteristics about the physical environment and social of the studied areas (Context Units) and the level of social organization of the territory to correlate with the dengue. An index of social organization of the territory of the contexted units was constructed based on the variables obtained by the Systematic Social Observation method, with multilevel analysis. To explain the individual behaviors, we should consider the individual, the aggregate and the context characteristics, that represent one approach with distinct hierarchical levels. The choice of the method is explained by the fact that the individual’s behavior being strongly influenced by the social groups they belong to and by physical-social environment where they live. The data collected was applied the coefficient of Pearson that tested the significance of the relation between the social organization of the territory and the dengue’s incidence. In the results obtained, became evident that exists one important correlation between the social organization of the territory and the population’s lifestyle with dengue’s occurrence in the searched areas.